Patch antenna for aircraft application 5G - Rafhanah Syahidah, Mohd Roslee (2021)
An overview of compact patch antennas for aircraft applications is presented. Antenna patches are integrated with the filters used in this project to improve communication on imitators. The antenna size is 21.5mm x 27mm combined with a 20mm x 25mm filter. Micro patch antennas are widely used because of their low profile, light weight, and plane structure. The integrated device is simple and designed for operation in 5 GHz suitable for aircraft communication. All properties e.g. return success, good gain, low insertion loss and stable radiation pattern make it suitable for use in this antenna integrated filter device for aircraft applications.